Penerapan Sistem Coretax dalam Proses Pelaporan Pajak Pertambahan Nilai: Studi Kasus pada PT Integra - Nasywa Roudhotul Firdaus; Ajeng Tita Nawangsari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study examines the implementation of Coretax in VAT reporting at PT Integra. Value Added Tax (VAT)is a major source of state revenue, thus motivating public oversight of tax reporting. To support this, the Directorate General of Taxes (DGT) introduced the Coretax Administration System (Coretax) as part of its digital tax transformation agenda. This study aims to analyze the implementation of Coretax in VAT reporting at PT Integra, identify emerging obstacles, and assess the system's role in improving company compliance. The results indicate that Coretax contributes to improving the timeliness, accuracy, and transparency of tax return reporting, while simplifying the audit process through more systematic data presentation. However, several challenges remain, such as data security risks, limited staff understanding, and technical system constraints. Overall, the implementation of Coretax is considered effective in improving tax administration and strengthening regulatory compliance, although full success still requires increased human resource competency and strengthened technological infrastructure.